on the History of Exploration of the Ilímuassaq Alkaline Intrusion, South Greenland. - Sørensen, H. (Meddelelser om Grønland, 1967)
The history of exploration of the Ilimaussaq alkaline intrusion is briefly reviewed. Geological and mineralogical investigations were first carried out by K. L. GIESECKE in 1806. Later K. J. V. STEENSTRUP, N. V. USSING, C. E. WEGMANN and a number of others have undertaken studies in and around the intrusion. The intrusion is mainly composed of peralkaline (agpaitic) nepheline syenites and is rich in rare elements and rare minerals. A number of minerals were first discovered in this intrusion, viz. ænigmatite, arfvedsonite, britholite, chalcothallite, epistolite, eudialyte, igdloite (= lueshite), ilimaussite, naujakasite, polylithionite, rinkite, schizolite, sodalite, sorensenite, steenstrup ine, tugtupite and ussingite. Renewed geological and mineralogical activity has taken place in Ilímaussaq during the last few years in connection with an examination of the economic geology of the area. A series of publications is in preparation. It was therefore considered to be of some value to present an account of the work until now and to prepare a list of the minerals so far identified and of the papers dealing with the intrusion. The bibliography, together with that prepared by BØGGILD (1953), contains the titles of all the papers on the mineralogy, geochemistry and geology of the intrusion known to the writer.